Airborne lidar measurements of ozone during the 1989 airborne Arctic stratospheric expedition - Kooi, Susan A.; Fenn, Marta A.; Browell, Edward V. (1991)
The NASA/NOAA Airborne Arctic Stratospheric Expedition (AASE) was conducted during the winter to study the conditions leading to possible ozone (O3) destruction in the wintertime Arctic stratosphere. As part of this experiment, the NASA-Langley airborne differential absorption lidar (DIAL) system was configured for operation on the NASA-Ames DS-8 aircraft to make measurements of O3 profiles from about 1 km above the aircraft to altitudes of 22 to 26 km. The airborne DIAL system remotely sensed O3 above the DC-8 by transmitting two laser beams at 10 Hz using wavelengths of 301.5 and 311 nm. Large scale distributions of O3 were obtained on 15 long range flights into the polar vortex during the AASE. Selected data samples are presented of O3 observed during these flights, general trends observed in O3 distributions, and correlations between these measurements and meteorological and chemical parameters. The O3 distribution observed on the first flight of the DC-8 into the polar vortex on Jan. 6 reflected the result of diabatic cooling of the air inside the vortex during the winter compared to the warmer air outside the vortex. On a potential temperature surface, the O3 mixing ratio generally increases when going from outside to inside the vortex.